Analysis of Organizational Performance Measurement Using a Balanced Scorecard Approach at the Garut Regency P2KBP3A Service - Kurniawati, Rina; Awaliyah, Pipit; Ramdhani, Abdullah; Hadiyanto, Nahdi; Fitriani, Leni (UNIVERSITAS PAKUAN, 2025)
Performance measurement is an evaluation of the implementation of activities to achieve the expected goals by assessing both financial and non-financial performance. The public perception of the programs carried out by the Garut Regency P2KBP3A Service still reflects stereotypes and outdated mindsets, which impact the failure to meet the expected program performance targets. This research aims to analyze how performance measurement is conducted at the Garut Regency P2KBP3A Service using the Balanced Scorecard model through four perspectives. The research applies a mixed-methods approach, combining qualitative methods using interactive data analysis and quantitative methods using descriptive analysis. Data collection was conducted through interviews, questionnaire distribution, and document analysis. The study results show that performance measurement at the Garut Regency P2KBP3A Service, viewed through the Balanced Scorecard model using four perspectives, is considered good. This indicates that the Garut Regency P2KBP3A Service has carried out programs according to its duties and responsibilities. However, some programs still fail to meet the targeted performance objectives.